2004
DOI: 10.7863/jum.2004.23.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Second-Trimester Sonographic and Biochemical Markers

Abstract: Objectives. To investigate correlations between sonographic soft markers and biochemical markers (human chorionic gonadotrophin, α-fetoprotein, and estriol) for Down syndrome in the second trimester of pregnancy. Methods. A total of 2183 women with apparently normal singleton fetuses who underwent second-trimester sonography (14-22 weeks) and maternal serum biochemical testing (triple test) were identified. Seven sonographic markers were recorded: nuchal fold thickness, humerus length, femur length, renal pyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…49,50 This pathway may also include chorionic gonadotropin, 51 the concentrations of which have been negatively associated with femur and humerus length. 52 Therefore, we may hypothesize that femur length differences may be associated with elevated maternal distress, although both groups may have been exposed to maternal distress. The lack of symptom rating scales data does not allow to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 This pathway may also include chorionic gonadotropin, 51 the concentrations of which have been negatively associated with femur and humerus length. 52 Therefore, we may hypothesize that femur length differences may be associated with elevated maternal distress, although both groups may have been exposed to maternal distress. The lack of symptom rating scales data does not allow to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal cortisol levels have been associated with maternal distress underlying unfavorable developmental outcomes 49,50 . This pathway may also include chorionic gonadotropin, 51 the concentrations of which have been negatively associated with femur and humerus length 52 . Therefore, we may hypothesize that femur length differences may be associated with elevated maternal distress, although both groups may have been exposed to maternal distress.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the presence of sonographic 'soft markers' in association with an isolated elevation of MShCG substantially increases Down syndrome risk remains to be determined. It has been demonstrated that MShCG and sonographic 'soft markers' are independent modifiers of Down syndrome risk (Souter et al, 2004), but only limited information on population-based studies to determine the screening efficacy of this approach have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…The congenital anomaly hospitalization significantly decreased among children, but the prematurity or condition from the perinatal periods did not decrease. The decrease in congenital anomaly may be related to the active screening program or more advanced ultrasound for congenital anomalies in recently [7,8]. In Taiwan, amniocentesis has been encouraged for pregnant women aged ≥ 35 years.…”
Section: Discussionmentioning
confidence: 99%